Mutual recognition agreements in international food trade - Malik, R.K.
(Es, En, Fr.)
Ilus., 4 ref.
Keywords: ACUERDOS COMERCIALES; ALIMENTOS; COMERCIO INTERNACIONAL; ITALIA; ALIMENTACION, NUTRICION Y AGRICULTURA